2001
DOI: 10.1161/01.str.32.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Initial Management of Stroke and Transient Ischemic Attack Across UK Health Regions From 1992 to 1996

Abstract: Background and Purpose-The aim of this study was to establish the difference in burden of cerebrovascular disease across the different health regions of the United Kingdom and to determine whether the initial management of new cases of stroke and transient ischemic attack (TIA) was uniform across the United Kingdom. Methods-The General Practice Research Database (GPRD) is a national database used for epidemiological studies. This was a cohort study identifying incident cases of stroke and TIA over a 5-year stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
(20 reference statements)
5
40
1
Order By: Relevance
“…It is therefore appropriate to derive risk estimates from data collected from general practice. The validity of the diagnostic data is important and GPRD data have been used in previous studies to estimate the prevalence of diabetes [32] and the incidence of stroke [33][34][35]. Our data using supporting evidence to confirm diagnosis among 80% of patients with a stroke code also agree with that of a previous GPRD cerebrovascular disease validation study [34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is therefore appropriate to derive risk estimates from data collected from general practice. The validity of the diagnostic data is important and GPRD data have been used in previous studies to estimate the prevalence of diabetes [32] and the incidence of stroke [33][34][35]. Our data using supporting evidence to confirm diagnosis among 80% of patients with a stroke code also agree with that of a previous GPRD cerebrovascular disease validation study [34].…”
Section: Discussionsupporting
confidence: 86%
“…The validity of the diagnostic data is important and GPRD data have been used in previous studies to estimate the prevalence of diabetes [32] and the incidence of stroke [33][34][35]. Our data using supporting evidence to confirm diagnosis among 80% of patients with a stroke code also agree with that of a previous GPRD cerebrovascular disease validation study [34]. We have also compared our rates of stroke in the comparison group without diabetes with that of the Oxford Vascular Study [36], and those in the diabetes group with those published by McAlpine et al [37], and the findings are remarkably consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence varies geographically, with the highest incidence (2.49 per 1000) in the former Yorkshire health region and the lowest (1.22 per 1000) in the Oxford region. 11 These figures suggest an annual UK incidence of over 100,000 new TIAs, a figure substantially in excess of the Stroke Association's estimate of between 30,000 and 40,000 TIAs per annum. 12 Moreover, the GPRD only records TIAs that come to medical attention, and is therefore likely to underestimate the true incidence of TIA: some patients do not seek medical advice because of the transient nature of their symptoms.…”
Section: Tia and Strokementioning
confidence: 94%
“…14 There are approximately 100,000 new cases of stroke per year in England and Wales. 11 Data from the GPRD for the years 1992-1996 indicate a mean annual age-adjusted UK incidence of new ischaemic stroke of 1.51 per 1000 population. This is supported by a prospective study carried out in Oxfordshire in the 1980s which found a crude annual incidence of clinically apparent first ever stroke of 1.60 per 1000 population [95% confidence interval (CI) 1.48 to 1.72] (2.00 per 1000 when adjusted by age and gender to the 1981 population of England and Wales).…”
Section: Tia and Strokementioning
confidence: 99%
“…17 The database is representative of all practices in England and Wales in terms of geographic distribution and size, and the age and sex distributions of the population included in it are similar to those of the whole population of the United Kingdom. 18 The information obtained for the database is anonymous. We obtained approval for our study from the scientific and ethics advisory group of the GPRD.…”
mentioning
confidence: 99%